Determinants of maternal success in long-term breastfeeding practice: A two-year duration - Cut Oktaviyana; Syarifah Masthura; Riska Marliza; Erlia Rosita (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: The World Health Organization (WHO) advises breastfeeding for up to two years to maximize a child’s growth and development, bolster their immune system, enhance nutritional intake, and protect against both acute illnesses and long-term health problems. Nevertheless, a study in the Tangeh Public Health Center of East Woyla District revealed that only around 21% of 474 mothers who initially practiced exclusive breastfeeding continued doing so until their child reached two years. Several factors a mother’s confidence in her ability to breastfeed (breastfeeding self-efficacy), encouragement from family members and healthcare professionals, and prevailing socio-cultural norms significantly impact continued breastfeeding up to two years. Purpose: To research investigated the impact of these factors on successful breastfeeding duration. Method: Data was collected via a quantitative cross-sectional study involving 79 participants and analyzed using the chi-square test and logistic regression. Results: The findings demonstrated that support from family, maternal breastfeeding self-efficacy, healthcare worker assistance, and socio-cultural influences all influence whether mothers breastfeed for the full two years. Conclusion: Ultimately, the study concluded that family support is the most critical factor in enabling mothers to breastfeed their babies for up to two years. Suggestion: It is critical for those in the healthcare field to consistently offer facts and support to the families of mothers who are breastfeeding. This guarantees that they receive constant help as they continue to breastfeed their babies.